Composite material as well as preparation method and application thereof
By depositing PtMTCP on a carbon paper substrate and performing cyclic voltammetry electrochemical treatment and ultrasonic treatment, a stable composite material is formed, which solves the problem of low NO gas detection sensitivity, and achieves efficient detection of low NO concentration and long-life sensor.
Patent Information
- Application Number
- CN202310791934.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2024-12-31
AI Technical Summary
It is difficult for the prior art to effectively detect NO gases with concentrations as low as ppb level, especially in electrochemical detection, the catalytic capacity of NO is poor, resulting in low detection sensitivity.
Using carbon paper as a carbon-containing substrate and PtMTCP composite material deposited thereon, a non-covalent hybrid composite is formed by cyclic voltammetry electrochemical treatment and ultrasonic treatment to enhance the binding of PtMTCP and carbon paper, and oxidizing groups are used. Coordinately promote NO oxidation and improve electrochemical detection performance.
It realizes high sensitivity detection of NO gas, extends the service life of the detection equipment, and meets the demand for low NO concentration detection.
Smart Images

Figure CN119224080A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of gas detection, and in particular relates to a composite material and a preparation method and application thereof. Background Art
[0002] Nitric oxide (NO) is a fat-soluble gas secreted by endothelial cells. It is produced by nitric oxide synthase (NOS) catalyzing L-arginine in the presence of oxygen, nicotinamide adenine dinucleotide phosphate (NADPH), flavin adenine dinucleotide (FAD), flavin mononucleotide (FMN) and tetrahydropterin. NO has multiple biological activities such as vasodilation, anti-platelet aggregation, and inhibition of vascular smooth muscle growth. NO participates in the regulation of many physiological processes in the human body. Among them, respiratory NO is produced by inflammatory cells, nasal and tracheal epithelial cells, and is currently a widely used molecular marker of airway inflammation.
[0003] The detection methods of NO include electron spin resonance spectroscopy, chemiluminescence and electrochemical methods. Among them, NO is a gaseous free radical with unpaired electrons and is a paramagnetic substance. Therefore, in theory, NO can be directly measured by electron spin resonance spectroscopy. However, since the single electron relaxation time of NO is too short, it is not easy to detect. It must be combined with another compound to produce a relatively stable complex before NO can be detected by electron spin resonance spectroscopy. The most studied chemiluminescence method is the use of Luminol-H 2 O 2 The luminescence system detects NO, and the reaction mechanism is NO and H 2 O 2 The reaction generates peroxynitrous acid (ONOOH), which oxidizes Luminol to produce chemiluminescence. The reaction needs to be carried out in an aqueous solution. Electrochemical detection technology has the advantages of high sensitivity, fast response speed and low price, and can achieve ppb-level response to NO. However, NO has a large overpotential at conventional electrodes, and its oxidation peak potential is often relatively positive, which is not conducive to electrochemical detection.
[0004] NO in exhaled gas can be used for inflammation diagnosis and treatment effect evaluation. The NO concentration in normal adult exhaled gas is 25ppb~50ppb, so there is a relatively high requirement for the detection limit of NO. Therefore, it is still necessary to develop a material with high sensitivity and low detection limit. Summary of the invention
[0005] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, the present invention provides a composite material, which can be used to detect NO gas with a concentration as low as ppb level.
[0006] The invention also provides a method for preparing the composite material.
[0007] The invention also provides an application of the composite material in NO gas detection.
[0008] The invention also provides a NO detection sensor.
[0009] A first aspect of the present invention provides a composite material, comprising a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein the surface of the carbon-containing substrate has oxidative groups.
[0010] One of the technical solutions of the present invention regarding the composite material has at least the following beneficial effects: If modified electrodes are used to achieve electrocatalytic oxidation of NO, the modifying materials that can be used include: carbon nanomaterials, metal and metal oxide nanoparticles, organic molecular polymers, and metal porphyrin polymers.
[0011] Carbon paper is a type of carbon material with the advantages of low price, large specific surface area and good conductivity. It can be used as a catalyst carrier. However, the catalytic ability of carbon paper for NO is relatively poor.
[0012] Metalloporphyrin (MPor) is a large class, in which the side chain groups of porphyrin can be replaced by other substituents, that is, the metal group can be replaced. At the same time, the metal groups are also different, such as iron, magnesium, etc. The precursor of porphyrin is porphine, and porphyrin can be formed by adding metal ions to porphine. meso-tetra (4-carboxyphenyl) porphine platinum chloride (Pt(II) meso-Tetra (4-carboxyphenyl) porphine, abbreviated as PtMTCP) is a kind of metalloporphyrin polymer, which has good catalytic ability for NO. It is generally combined with carbon materials through π-π forces. π-π stacking is a special spatial arrangement of aromatic compounds, which refers to a weak interaction that often occurs between aromatic rings. It usually exists between two molecules that are relatively electron-rich and electron-deficient. It is a non-covalent bond interaction that is as important as hydrogen bonds. π-stacking is a weak interaction between π-electron conjugated systems under certain special spatial arrangements. The forms of π-stacking include: π-π, cation-π, anion-π, halogen bond-π and CH-π stacking. However, the π-π stacking bonding method is not reliable and is prone to fall off after long-term use.
[0013] The composite material of the present invention comprises a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, so that when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP on NO with the carbon-containing substrate with a large specific surface area, thereby achieving a more excellent electrochemical detection performance for NO.
[0014] According to some embodiments of the invention, the carbon-containing substrate comprises carbon paper.
[0015] According to some embodiments of the present invention, the carbon-containing substrate has a thickness ranging from 0.4 to 100 μm.
[0016] According to some embodiments of the invention, the carbon-containing substrate and the PtMTCP are chemically bonded via a non-covalent bond.
[0017] According to some embodiments of the invention, the oxidizing group comprises a carboxyl group.
[0018] The second aspect of the present invention provides a method for preparing the composite material, comprising the following steps: using two carbon-containing substrates as an anode and a cathode, respectively, immersing them in an alkaline solution of PtMTCP, and simultaneously performing cyclic voltammetry electrochemical treatment and ultrasonic treatment to obtain two sheets of the composite material.
[0019] A technical solution in the method for preparing a composite material of the present invention has at least the following beneficial effects: The preparation method of the composite material of the present invention combines cyclic voltammetry electrochemical treatment and ultrasonic treatment, wherein the cyclic voltammetry electrochemical treatment not only oxidizes the surface of the carbon-containing substrate, and the generated oxidized groups can promote the oxidation of NO, but also deposits PtMTCP on the surface of the carbon-containing substrate containing the oxidized groups through electrochemical deposition to form a non-covalent hybrid complex. At the same time, the ultrasonic treatment can increase the specific surface area of the carbon-containing substrate, and make the PtMTCP with poor binding force fall off, so that the surface uniformity of the final product is better.
[0020] Cyclic voltammetry electrochemical treatment directly forms a dense PtMTCP film on the surface of the carbon-containing substrate, which reduces the specific surface area of the carbon-containing substrate, thereby reducing the sensitivity to NO response. At the same time, ultrasonic treatment can make the surface structure of the carbon-containing substrate porous, retaining the large specific surface area characteristics of the carbon-containing substrate.
[0021] The preparation method of the present invention belongs to a one-step technology, the process is simpler and the preparation time is saved.
[0022] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.
[0023] According to some embodiments of the present invention, during the preparation process, the electrolyte is generally a conductive substance dissolved in a solvent, and according to actual conditions, electrochemical modification materials can be added, including metal salts and small molecule organic substances. If there is no special explanation, the solvent of the electrolyte in the electrochemical experiment is generally water, and the conductive substance can be an acid, an alkali or a salt.
[0024] According to some embodiments of the present invention, during the preparation process, two carbon-containing substrates can be used as cathode and anode, respectively, fixed in an electrolytic cell, a sodium hydroxide solution containing PtMTCP is added, and then the electrolytic cell is placed in an ultrasonic cleaner. In order to ensure the ultrasonic effect, the water surface should be above the liquid surface of the electrolytic cell. The electrochemical cyclic voltammetry and the ultrasonic cleaner are started simultaneously, wherein the electrochemical cyclic voltammetry oxidizes the carbon-containing matrix into a carboxylated carbon-containing matrix, and forms a non-covalent hybrid composite material through electrochemical deposition and π-π forces.
[0025] After the electrochemical ultrasonic preparation is completed, the two composite materials are rinsed with deionized water to remove the sodium hydroxide and undeposited PtMTCP on the surface. The deionized water is rinsed until it becomes neutral, and the composite materials are dried.
[0026] The composite material can also be cut into a circle or other shape, pasted on a polytetrafluoroethylene film, and used as a working electrode to form a NO sensor with a mercurous sulfate reference electrode, a platinum counter electrode, and a sulfuric acid electrolyte to detect NO.
[0027] Cutting into a circle can maximize the catalytic area and fit the circular channel opening of the H-type electrolytic cell.
[0028] The main function of the polytetrafluoroethylene film is "hydrophobic and breathable". "Hydrophobic" means preventing the water in the electrolytic cell from evaporating and preventing external water from entering, thereby changing the electrolyte concentration and affecting performance. "Breathable" means allowing external NO gas to enter the sensor for detection.
[0029] At present, polytetrafluoroethylene film is the best film resistant to sulfuric acid corrosion and has become industrialized.
[0030] According to some embodiments of the present invention, the solvent is water, the conductive substance is sodium hydroxide, and the electrochemical modification material is PtMTCP.
[0031] According to some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of PtMTCP is 0.1 mmol / L to 10 mmol / L.
[0032] According to some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of PtMTCP is 0.1 mmol / L to 2 mmol / L.
[0033] According to some embodiments of the present invention, in the alkaline solution of PtMTCP, the base comprises sodium hydroxide.
[0034] According to some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of sodium hydroxide is 0.01 mmol / L~0.1 mmol / L.
[0035] According to some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of sodium hydroxide is 0.01 mmol / L to 0.05 mmol / L.
[0036] PtMTCP is generally a solid powder that dissolves in alkaline solution.
[0037] According to some embodiments of the present invention, two carbon-containing substrates are used as an anode and a cathode, respectively, and immersed in an alkaline solution of PtMTCP. The two carbon-containing substrates can be arranged in parallel, which is beneficial to charge transfer.
[0038] According to some embodiments of the present invention, the potential of the cyclic voltammetry electrochemical treatment is -1V~1.5V.
[0039] According to some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s to 0.2 V / s.
[0040] According to some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s to 0.05 V / s.
[0041] According to some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s, 0.05 V / s, 0.2 V / s or a range formed by any two of these values.
[0042] According to some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 to 300.
[0043] According to some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 to 100.
[0044] According to some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 cycles, 100 cycles, 300 cycles, or a range formed by any two of these values.
[0045] Cyclic voltammetry (CV) is a method of changing the potential to obtain the direction of the redox current. It is mainly carried out by applying a cyclic potential, from a starting potential to an end potential at a fixed rate, and then changing back to the starting potential at the same rate. This is a cycle. The CV graph obtained from the analysis of reversible oxidation reactants can be drawn. When scanning from a low potential to a high potential, the analyte will produce an anodic peak of the oxidation current. This CV graph helps to determine at what potential the oxidation reaction will occur.
[0046] Cyclic voltammetry uses a three-electrode system, that is, three electrodes are passed into the solution to be tested, namely the working electrode (indicator electrode), the reference electrode and the auxiliary electrode.
[0047] According to some embodiments of the present invention, the power of the ultrasonic treatment is 10W~80W.
[0048] According to some embodiments of the present invention, the power of the ultrasonic treatment is 10W~20W.
[0049] According to some embodiments of the present invention, the power of the ultrasonic treatment is 10 W, 20 W, 80 W or a range formed by any two of these values.
[0050] The third aspect of the present invention provides application of the composite material in NO gas detection.
[0051] A technical solution of the present invention regarding the application of composite materials in NO gas detection has at least the following beneficial effects: When the composite material of the present invention is used for NO gas detection, it has all the beneficial effects of the composite material. Specifically, since the composite material includes a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force, and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, thus, when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP for NO with the carbon-containing substrate with a large specific surface area, and achieves a more excellent electrochemical detection performance for NO.
[0052] A fourth aspect of the present invention provides a NO detection sensor, comprising the composite material.
[0053] One of the technical solutions of the present invention regarding the NO detection sensor has at least the following beneficial effects: The NO detection sensor of the present invention has all the beneficial effects of the composite material due to the use of the composite material of the present invention. Specifically, the composite material includes a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force, and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, so that when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP for NO with the carbon-containing substrate with a large specific surface area, and achieves a more excellent electrochemical detection performance for NO. Ultimately, the performance of the sensor is better.
[0054] According to some embodiments of the present invention, the NO detection sensor comprises: A sensing film, the sensing film comprising a base film and the composite material arranged on the surface of the base film; The electrolytic cell is divided into a first electrolytic cell and a second electrolytic cell by the sensing membrane, the NO gas to be detected is introduced into the first electrolytic cell, and the base membrane side of the sensing membrane faces the first electrolytic cell.
[0055] According to some embodiments of the present invention, the electrolytic cell may be an H-type electrolytic cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 1 is a cyclic voltammogram of the composite material according to an embodiment of the present invention.
[0057] Figure 2 It is a NO response curve diagram of the composite material of the embodiment of the present invention as a working electrode.
[0058] Figure 3 This is the NO response curve of carbon paper as the working electrode.
[0059] Figure 4 This is a NO response curve of the composite material of Comparative Example 1 as a working electrode.
[0060] Figure 5 This is a NO response curve of the composite material of Comparative Example 2 as a working electrode. Implementation
[0061] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0062] In some embodiments of the present invention, the present invention provides a composite material, including a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein the surface of the carbon-containing substrate has oxidative groups.
[0063] It can be understood that if a modified electrode is used to achieve electrocatalytic oxidation of NO, the modification materials that can be used include: carbon nanomaterials, metal and metal oxide nanoparticles, organic molecular polymers and metal porphyrin polymers.
[0064] Carbon paper is a type of carbon material with the advantages of low price, large specific surface area and good conductivity. It can be used as a catalyst carrier. However, the catalytic ability of carbon paper for NO is relatively poor.
[0065] It should be noted that metal porphyrin (MPor) is a large category, in which the side chain groups of porphyrin can be replaced by other substituents, that is, the metal group can be replaced. At the same time, the metal groups are also different, such as iron, magnesium, etc. The precursor of porphyrin is porphine, and porphyrin can be formed by adding metal ions to porphine. meso-tetra (4-carboxyphenyl) porphine platinum chloride (Pt(II) meso-Tetra (4-carboxyphenyl) porphine, abbreviated as PtMTCP) is a type of metal porphyrin polymer with good catalytic ability for NO. It is generally combined with carbon materials through π-π forces. π-π stacking is a special spatial arrangement of aromatic compounds, referring to a weak interaction that often occurs between aromatic rings. It usually exists between two molecules that are relatively electron-rich and electron-deficient. It is a non-covalent bond interaction that is as important as hydrogen bonds. π-stacking is a weak interaction between π-electron conjugated systems under certain special spatial arrangements. The forms of π-stacking include: π-π, cation-π, anion-π, halogen bond-π and CH-π stacking. However, the π-π stacking bonding method is not reliable and is prone to fall off after long-term use.
[0066] It can be understood that the composite material of the present invention includes a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly bonded to carbon paper through electrochemical deposition and π-π force and is not easy to fall off; in addition, the surface of the carbon-containing substrate has oxidizing groups, and the oxidizing groups and PtMTCP can synergistically promote the oxidation of NO. Therefore, when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer.
[0067] It can also be understood that the composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP for NO with a carbon-containing substrate with a large specific surface area, thereby achieving a more excellent electrochemical detection performance for NO.
[0068] In some embodiments of the present invention, the carbon-containing substrate comprises carbon paper.
[0069] In some embodiments of the present invention, the thickness of the carbon-containing substrate is in the range of 0.4-100 μm.
[0070] In some embodiments of the present invention, the carbon-containing substrate and PtMTCP are chemically bonded via non-covalent bonds.
[0071] In some embodiments of the present invention, the reactive group comprises a carboxyl group.
[0072] In some other embodiments of the present invention, the present invention provides a method for preparing a composite material, comprising the following steps: two carbon-containing substrates are used as an anode and a cathode, respectively, and immersed in an alkaline solution of PtMTCP, and cyclic voltammetry electrochemical treatment and ultrasonic treatment are performed simultaneously to obtain two composite materials of the present invention.
[0073] It can be understood that the preparation method of the composite material of the present invention combines cyclic voltammetry electrochemical treatment and ultrasonic treatment, wherein the cyclic voltammetry electrochemical treatment not only oxidizes the surface of the carbon-containing substrate, and the generated oxidized groups can promote the oxidation of NO, but also deposits PtMTCP on the surface of the carbon-containing substrate containing oxidized groups by electrochemical deposition to form a non-covalent hybrid complex. At the same time, ultrasonic treatment can increase the specific surface area of the carbon-containing substrate, and make the PtMTCP with poor binding force fall off, and the surface uniformity of the final product is better.
[0074] Cyclic voltammetry electrochemical treatment directly forms a dense PtMTCP film on the surface of the carbon-containing substrate, which reduces the specific surface area of the carbon-containing substrate, thereby reducing the sensitivity to NO response. At the same time, ultrasonic treatment can make the surface structure of the carbon-containing substrate porous, retaining the large specific surface area characteristics of the carbon-containing substrate.
[0075] The preparation method of the present invention belongs to a one-step technology, the process is simpler and the preparation time is saved.
[0076] The preparation method of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.
[0077] In some embodiments of the present invention, during the preparation process, the electrolyte is generally a conductive substance dissolved in a solvent, and according to actual conditions, electrochemical modification materials may be added, including metal salts and small molecule organic substances. If there is no special explanation, the solvent of the electrolyte in the electrochemical experiment is generally water, and the conductive substance may be an acid, an alkali or a salt.
[0078] In some embodiments of the present invention, during the preparation process, two carbon-containing substrates can be used as cathode and anode, respectively, fixed in an electrolytic cell, a sodium hydroxide solution containing PtMTCP is added, and then the electrolytic cell is placed in an ultrasonic cleaner. In order to ensure the ultrasonic effect, the water surface should be above the liquid surface of the electrolytic cell. The electrochemical cyclic voltammetry and the ultrasonic cleaner are started at the same time, wherein the electrochemical cyclic voltammetry oxidizes the carbon-containing matrix into a carboxylated carbon-containing matrix, and forms a non-covalent hybrid composite material through electrochemical deposition and π-π forces.
[0079] In some embodiments of the present invention, after the electrochemical ultrasonic preparation is completed, the two composite materials are rinsed with deionized water to remove the sodium hydroxide and undeposited PtMTCP on the surface, and the deionized water is rinsed until it becomes neutral, and the composite materials are dried.
[0080] In some embodiments of the present invention, the composite material can be cut into a circle or other shape, pasted on a polytetrafluoroethylene film, and used as a working electrode to form a NO sensor with a mercurous sulfate reference electrode, a platinum counter electrode, and a sulfuric acid electrolyte to detect NO.
[0081] It should be noted that cutting into a circle can maximize the catalytic area and fit the circular channel opening of the H-type electrolytic cell.
[0082] The main function of the polytetrafluoroethylene film is "hydrophobic and breathable". "Hydrophobic" means preventing the water in the electrolytic cell from evaporating and preventing external water from entering, thereby changing the electrolyte concentration and affecting performance. "Breathable" means allowing external NO gas to enter the sensor for detection.
[0083] It should be noted that currently polytetrafluoroethylene film is the best film resistant to sulfuric acid corrosion and has become industrialized.
[0084] In some embodiments of the present invention, the solvent is water, the conductive substance is sodium hydroxide, and the electrochemical modification material is PtMTCP.
[0085] In some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of PtMTCP is 0.1 mmol / L to 10 mmol / L.
[0086] In some embodiments of the present invention, in the alkaline solution of PtMTCP, the concentration of PtMTCP is 0.1 mmol / L to 2 mmol / L.
[0087] In some embodiments of the present invention, in the alkaline solution of PtMTCP, the base comprises sodium hydroxide.
[0088] In some embodiments of the present invention, the concentration of sodium hydroxide in the alkaline solution of PtMTCP is 0.01 mmol / L~0.1 mmol / L.
[0089] In some embodiments of the present invention, the concentration of sodium hydroxide in the alkaline solution of PtMTCP is 0.01 mmol / L to 0.05 mmol / L.
[0090] PtMTCP is generally a solid powder that dissolves in alkaline solution.
[0091] In some embodiments of the present invention, two carbon-containing substrates are used as an anode and a cathode, respectively, and immersed in an alkaline solution of PtMTCP. The two carbon-containing substrates can be arranged in parallel, which is beneficial to charge transfer.
[0092] In some embodiments of the present invention, the potential of the cyclic voltammetry electrochemical treatment is -1V~1.5V.
[0093] In some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s to 0.2 V / s.
[0094] In some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s to 0.05 V / s.
[0095] In some embodiments of the present invention, the scan rate of the cyclic voltammetry electrochemical treatment is 0.01 V / s, 0.05 V / s, 0.2 V / s, or a range formed by any two of these values.
[0096] In some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 to 300.
[0097] In some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 to 100.
[0098] In some embodiments of the present invention, the number of cycles of the cyclic voltammetry electrochemical treatment is 30 cycles, 100 cycles, 300 cycles, or a range formed by any two of these values.
[0099] Cyclic voltammetry (CV) is a method of changing the potential to obtain the direction of the redox current. It is mainly carried out by applying a cyclic potential, from a starting potential to an end potential at a fixed rate, and then changing back to the starting potential at the same rate. This is a cycle. The CV graph obtained from the analysis of reversible oxidation reactants can be drawn. When scanning from a low potential to a high potential, the analyte will produce an anodic peak of the oxidation current. This CV graph helps to determine at what potential the oxidation reaction will occur.
[0100] Cyclic voltammetry uses a three-electrode system, that is, three electrodes are passed into the solution to be tested, namely the working electrode (indicator electrode), the reference electrode and the auxiliary electrode.
[0101] In some embodiments of the present invention, the power of ultrasonic treatment is 10W~80W.
[0102] In some other embodiments of the present invention, the power of ultrasonic treatment is 10W~20W.
[0103] In some embodiments of the present invention, the power of ultrasonic treatment is 10 W, 20 W, 80 W or a range formed by any two values therein.
[0104] In some other embodiments of the present invention, the present invention provides use of the composite material in NO gas detection.
[0105] It can be understood that when the composite material of the present invention is used for NO gas detection, it has all the beneficial effects of the composite material. Specifically, since the composite material includes a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force, and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, thus, when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP for NO with the carbon-containing substrate with a large specific surface area, and achieves a more excellent electrochemical detection performance for NO.
[0106] In some other embodiments of the present invention, a NO detection sensor is provided, comprising the composite material of the present invention.
[0107] It can be understood that the NO detection sensor of the present invention has all the beneficial effects of the composite material due to the use of the composite material of the present invention. Specifically, since the composite material includes a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force, and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, thus, when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP for NO with the carbon-containing substrate with a large specific surface area, and achieves a more excellent electrochemical detection performance for NO. Ultimately, the performance of the sensor is better.
[0108] In some embodiments of the present invention, the NO detection sensor comprises: A sensing film, the sensing film comprising a base film and a composite material arranged on the surface of the base film; The electrolytic cell is divided into a first electrolytic cell and a second electrolytic cell by a sensing membrane. The NO gas to be measured is introduced into the first electrolytic cell, and the base membrane side of the sensing membrane faces the first electrolytic cell.
[0109] In some embodiments of the present invention, the electrolytic cell may be an H-type electrolytic cell.
[0110] The technical solution of the present invention will be better understood with reference to specific embodiments below. Example
[0111] In this embodiment, a composite material is first prepared.
[0112] Among the raw materials, carbon paper was purchased from Shengernuo Energy, with specifications of HCP010N, hydrophilic, 21×20 cm.
[0113] The specific process is: Step 1: Two pieces of carbon paper are used as the anode and cathode, respectively, and fixed in parallel in the electrolytic cell, and then an electrolyte is added to the electrolytic cell. The electrolyte composition is 5mmol / L PtMTCP and 0.05mmol / L sodium hydroxide solution; Step 2: Place the electrolytic cell in step 1 into an ultrasonic cleaner. The water surface should be above the liquid level of the electrolytic cell. Fix the reference electrode clamp and the counter electrode clamp of the electrochemical workstation to carbon paper, and fix the working electrode clamp to another piece of carbon paper to form a closed loop. The electrochemical cyclic voltammetry and the ultrasonic cleaner are started at the same time. The parameters of the cyclic voltammetry are as follows: the potential range is -1~1.5V, the scanning speed is 0.05V / s, and the number of cycles is 100; the power of the ultrasonic cleaner is 20W; Step 3: After the electrochemical ultrasonic preparation is completed, the two composite materials are rinsed with deionized water to remove the sodium hydroxide and undeposited PtMTCP on the surface. The deionized water is rinsed until it is neutral. The composite materials are dried, cut into circles with a diameter of 15 mm, and pasted on a hydrophobic and breathable polytetrafluoroethylene film for use.
[0114] Then, the prepared composite material is assembled into a preliminary sensor. The specific process is as follows: Step 4: The composite material of step 3 is used as a working electrode and sandwiched between the two channels of the H-type electrolytic cell. The carbon paper side of the composite material is in the same electrolytic cell with the mercurous sulfate reference electrode, the platinum counter electrode and the sulfuric acid electrolyte with a mass fraction of 30%wt; the polytetrafluoroethylene film side is in another electrolytic cell, which is used to pass NO gas. In this way, a preliminary NO sensor is assembled.
[0115] After that, the sensor is tested for performance. The specific process is as follows: First, cyclic voltammetry was used to characterize the NO sensor for the purpose of electropolymerizing PtMTCP that was still unpolymerized on the surface of the composite.
[0116] like Figure 1 As shown, with the increase of cyclic voltammetry cycles, the reduction peak at -0.2 V gradually becomes smaller, while the oxidation peak at -0.1 V and the reduction peak at -0.5 V gradually increase, indicating that the residual PtMTCP gradually electropolymerizes.
[0117] The current magnitudes of the oxidation peak at -0.1V and the reduction peak at -0.5V are similar, which shows a certain degree of reversibility and belongs to the Pt in PtMTCP. 2+ The electrochemical reaction of Pt 2+ It can accept the electrons lost by NO oxidation and promote the reaction of NO.
[0118] A voltage of 0.35 V was applied to the NO sensor until the baseline was stable, and then 20, 50, 100, 200 and 500 ppb NO gas was gradually introduced.
[0119] The results are as follows Figure 2 As shown in the figure, as the NO concentration increases, the current also increases, indicating that NO undergoes an electrochemical oxidation reaction.
[0120] NO sensor with carbon paper as working electrode (reference Figure 3 As shown in the figure, the sensitivity of the NO sensor using the composite material of the present invention as the working electrode is 1.722 nA / ppb, and the sensitivity of the carbon paper working electrode is 0.491 nA / ppb, which is enhanced by 3.5 times, indicating that the composite material of the present invention has very excellent electrochemical catalytic performance.
[0121] According to the 3×standard deviation / sensitivity principle, it can be calculated that the resolution of the NO sensor using the composite material of the present invention as the working electrode is 5.62 ppb, which meets the detection requirements of NO in oral exhaled breath.
[0122] The difference between this comparative example and the embodiment is that no ultrasonic effect is applied during the preparation process.
[0123] In this comparative example, a composite material was first prepared.
[0124] Among the raw materials, carbon paper was purchased from Shengernuo Energy, with specifications of HCP010N, hydrophilic, 21×20 cm.
[0125] The specific process is: Step 1: Two pieces of carbon paper are used as the anode and cathode, respectively, and fixed in parallel in the electrolytic cell, and then an electrolyte is added to the electrolytic cell. The electrolyte composition is 5mmol / L PtMTCP and 0.05mmol / L sodium hydroxide solution; Step 2: Fix the reference electrode and counter electrode clips of the electrochemical workstation to carbon paper, and fix the working electrode clip to another piece of carbon paper to form a closed loop, and start the electrochemical cyclic voltammetry. The parameters of the cyclic voltammetry are as follows: the potential range is -1~1.5V, the scanning speed is 0.05V / s, and the number of cycles is 100; Step 3: After the cyclic voltammetry electrochemical treatment, the two composite materials were rinsed with deionized water to remove the sodium hydroxide and undeposited PtMTCP on the surface. The deionized water was rinsed until it was neutral. The composite materials were dried, cut into circles with a diameter of 15 mm, and pasted on a hydrophobic and breathable polytetrafluoroethylene film for later use.
[0126] Then, the prepared composite material is assembled into a preliminary sensor. The specific process is as follows: Step 4: The composite material of step 3 is used as a working electrode and sandwiched between the two channels of the H-type electrolytic cell. The carbon paper side of the composite material is in the same electrolytic cell with the mercurous sulfate reference electrode, the platinum counter electrode and the sulfuric acid electrolyte with a mass fraction of 30%wt; the polytetrafluoroethylene film side is in another electrolytic cell, which is used to pass NO gas. In this way, a preliminary NO sensor is assembled.
[0127] Afterwards, the sensor performance is verified.
[0128] The results are as follows Figure 4 As shown, the sensitivity of the NO sensor with the composite material of this comparative example as the working electrode is 1.274nA / ppb, and the sensitivity of the carbon paper working electrode is 0.491nA / ppb, which is enhanced by 2.6 times, indicating that the electrochemical catalytic performance of the composite material of this comparative example is not as good as the composite material prepared in the embodiment.
[0129] According to the 3×standard deviation / sensitivity principle, it can be calculated that the resolution of the NO sensor using the composite material of the present invention as the working electrode is 10.44 ppb, which is lower than that of the composite material prepared in the example.
[0130] The difference between this comparative example and the embodiment is that no cyclic voltammetry electrochemical treatment is performed during the preparation process.
[0131] Among the raw materials, carbon paper was purchased from Shengernuo Energy, with specifications of HCP010N, hydrophilic, 21×20 cm.
[0132] The specific process is: Step 1: Fix the carbon paper in the electrolytic cell, and then add the electrolyte into the electrolytic cell, wherein the electrolyte consists of 5 mmol / L PtMTCP and 0.05 mmol / L sodium hydroxide solution; Step 2: Place the electrolytic cell in step 1 into the ultrasonic cleaner. The water level should be above the liquid level of the electrolytic cell. Start the ultrasonic cleaner. The power of the ultrasonic cleaner is 20W.
[0133] Step 3: After the same ultrasonic treatment time as in Example 1, the composite material is rinsed with deionized water to remove the sodium hydroxide on the surface and the undeposited PtMTCP, and the deionized water is rinsed until it is neutral. The composite material is dried, cut into a circle with a diameter of 15 mm, and pasted on a hydrophobic and breathable polytetrafluoroethylene film for use.
[0134] Then, the prepared composite material is assembled into a preliminary sensor. The specific process is as follows: Step 4: The composite material of step 3 is used as a working electrode and sandwiched between the two channels of the H-type electrolytic cell. The carbon paper side of the composite material is in the same electrolytic cell with the mercurous sulfate reference electrode, the platinum counter electrode and the sulfuric acid electrolyte with a mass fraction of 30%wt; the polytetrafluoroethylene film side is in another electrolytic cell, which is used to pass NO gas. In this way, a preliminary NO sensor is assembled.
[0135] After that, the sensor is tested for performance. The specific process is as follows: The results are as follows Figure 5 As shown, the sensitivity of the NO sensor with the composite material of this comparative example as the working electrode is 0.676nA / ppb, and the sensitivity of the carbon paper working electrode is 0.491nA / ppb, which is only enhanced by 1.4 times, indicating that the electrochemical catalytic performance of the composite material of this comparative example is significantly lower than that of the composite material prepared in the embodiment.
[0136] According to the 3×standard deviation / sensitivity principle, it can be calculated that the resolution of the NO sensor using the composite material of the present invention as the working electrode is 17.03 ppb, which is significantly lower than the composite material prepared in the example.
[0137] The composite material of the present invention comprises a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein PtMTCP is more firmly combined with carbon paper through electrochemical deposition and π-π force and is not easy to fall off; in addition, the surface of the carbon-containing substrate has an oxidizing group, and the oxidizing group and PtMTCP can synergistically promote the oxidation of NO, so that when the composite material is used for NO gas detection, the detection performance is more stable and the service life is longer. The composite material of the present invention combines the excellent electrocatalytic performance of PtMTCP on NO with the carbon-containing substrate with a large specific surface area, thereby achieving a more excellent electrochemical detection performance for NO.
[0138] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A composite material, characterized in that: The invention comprises a carbon-containing substrate and PtMTCP deposited on the carbon-containing substrate, wherein the surface of the carbon-containing substrate has oxidative groups.
2. The composite material according to claim 1, characterized in that The carbon-containing substrate includes carbon paper.
3. The composite material according to claim 1, characterized in that The carbon-containing substrate and the PtMTCP are chemically bonded via non-covalent bonds.
4. A method for preparing the composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Two carbon-containing substrates were used as an anode and a cathode, respectively, and immersed in an alkaline solution of PtMTCP. Cyclic voltammetry electrochemical treatment and ultrasonic treatment were performed simultaneously to obtain two sheets of the composite material.
5. The method according to claim 4, characterized in that In the alkaline solution of PtMTCP, the concentration of PtMTCP is 0.1 mmol / L to 10 mmol / L.
6. The method according to claim 4, characterized in that The potential of the cyclic voltammetry electrochemical treatment is -1V~1.5V; and / or, the scanning speed of the cyclic voltammetry electrochemical treatment is 0.01V / s~0.2V / s; and / or, the number of cycles of the cyclic voltammetry electrochemical treatment is 30~300.
7. The method according to claim 4, characterized in that The power of the ultrasonic treatment is 10W~80W.
8. Use of the composite material according to any one of claims 1 to 3 in NO gas detection.
9. A NO detection sensor, characterized in that: The composite material comprises the composite material according to any one of claims 1 to 3.
10. The NO detection sensor according to claim 9, characterized in that: include: A sensing film, the sensing film comprising a base film and the composite material arranged on the surface of the base film; The electrolytic cell is divided into a first electrolytic cell and a second electrolytic cell by the sensing membrane, the NO gas to be detected is introduced into the first electrolytic cell, and the base membrane side of the sensing membrane faces the first electrolytic cell.